PENGARUH MOTIVASI KERJA DAN KOMUNIKASI KERJA TERHADAP PRESTASI KERJA YANG DI MODERASI OLEH KEPRIBADIAN KARYAWAN PADA PERUM PERUMNAS REGIONAL I MEDAN - Rina Hartaci Nasution; Kiki Farida Ferine; Henry Aspan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Human quality as a workforce is the basic capital to create good performance. Work performance for employees in a company is important, as well as creating a work performance is a dream and hope that every company must achieve. Work motivation, work communication and employee personality are some of the factors that affect the work performance of an employee in a company. This research was conducted at Perum Perumnas Regional I Medan, which is a State-Owned Enterprise in the form of a National-based Public Company. The research population of Perum Perumnas Regional I Medan employees as the sample is 78 employees. This study aims to determine whether there is an influence of work motivation, work communication, and employee personality on the work performance of employees who are moderated at Perum Perumnas Regional I Medan. This research method uses a moderating 2 model. The results of the study contained 2 (two) independent variables, namely work motivation and work communication, 1 (one) moderating variable, namely the personality of the employee, and 1 (one) dependent variable which had a significant influence on the work performance of Perum Perumnas Regional I Medan. Suggestions submitted to the company's management, should pay attention to the role of its employees, in order to improve employee performance. Keywords: Motivation, Communication, personality , work performance.